Risk Factors for Recurrence of Symptomatic Common Bile Duct Stones after Cholecystectomy - Ju Hyun Oak; Chang Nyol Paik; Woo Chul Chung; Kang-Moon Lee; Jin Mo Yang (Gastroenterology Research and Practice)
Purpose. The recurrence of CBD stone is still observed in a considerable number of patients. The study was to evaluate the risk factors for recurrence of symptomatic CBD stone in patients who underwent cholecystectomy after the removal of CBD stone. Methods. The medical records of patients who underwent removal of CBD stone with subsequent cholecystectomy were reviewed. The risk factors for the recurrence of symptomatic CBD stone were compared between the recurrence and the nonrecurrence group. Results. The mean follow-up period was 40.6 months. The recurrence of symptomatic CBD stones was defined as the detection of bile duct stones no sooner than 6 months after complete clearance of CBD stones, based on symptoms or signs of biliary complication. 144 patients (68 males, 47.2%) were finally enrolled and their mean age was 59.8 (range: 26~86) years. The recurrence of CBD stone occurred in 15 patients (10.4%). The mean period until first recurrence was 25.9 months. The presence of type 1 or 2 periampullary diverticulum and multiple CBD stones were the independent risk factors. Conclusion. For the patients with type 1 or 2 periampullary diverticulum or multiple CBD stones, careful followup is needed for the risk in recurrence of symptomatic CBD stone.